2020
DOI: 10.1177/2324709620933422
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Diagnosis of Bilateral Pleural Effusion and Multiple Mediastinal Lymphadenopathies Includes Kikuchi-Fujimoto Disease

Abstract: Kikuchi-Fujimoto disease is an uncommon lymphohistiocytic disorder that frequently presents with acute or subacute clinical disease course. Cervical lymphadenopathy is the most common involved lymph node. Very rare cases of pathologic diagnosis of Kikuchi-Fujimoto disease with bilateral pleural effusion and multiple mediastinal lymphadenopathies have been reported in the literature. In this article, we report the case of a 60-year-old male presented with bilateral pleural effusion and multiple mediastinal lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Some studies show female preponderance (4:1) in KFD [ 5 ]. However, new investigations have reported equal distribution of the disease among the male and female Asian populations [ 2 ]. Additionally, some rare case studies in the United States (US) and Europe found that the disease has been distributed in all racial groups and ethnic groups [ 6 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies show female preponderance (4:1) in KFD [ 5 ]. However, new investigations have reported equal distribution of the disease among the male and female Asian populations [ 2 ]. Additionally, some rare case studies in the United States (US) and Europe found that the disease has been distributed in all racial groups and ethnic groups [ 6 ].…”
Section: Reviewmentioning
confidence: 99%
“…A low-grade fever may be reported in 50% of KFD patients, along with respiratory symptoms such as cough and headache. Less frequent symptoms of KFD include skin rash, weight loss, nausea, vomiting, sore throat, and night sweats [ 1 , 2 , 10 ]. Apart from fever and tender cervical lymphadenopathy, leukopenia has been detected in 50% of KFD patients.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations